The Effect of Financial Literacy and Risk Perception on Investment Decisions Among Generation Z - Azolla Degita Azis; Iin Safariah; Ernawati Ernawati (Jurnal Publikasi Ilmu Manajemen, 2026)
This study aims to analyse the effects of financial literacy and risk perception on investment decisions among Generation Z in Jambi. A quantitative approach with an explanatory and cross-sectional design was employed. Data were collected using a five-point Likert-scale questionnaire administered to 100 respondents selected through purposive sampling, based on the criteria of residing in Jambi and having invested or considered investing in financial products. The data were analysed using multiple linear regression with IBM SPSS Statistics after validity, reliability, and classical assumption tests were conducted. The results show that financial literacy has a positive and significant effect on investment decisions, whereas risk perception has a negative and significant effect. Simultaneously, both variables significantly affect investment decisions and explain 37.2% of their variation. Financial literacy was identified as the most dominant predictor of respondents’ investment decisions. These findings imply that universities, financial institutions, securities companies, and policymakers should develop practical financial education programmes that improve investment knowledge while promoting a balanced understanding of risk, thereby enabling Generation Z to make rational, responsible, and sustainable investment decisions.